Deformation and Failure Characteristics of Loading and Unloading Rock Based on Volume Crack Strain - Liu, Xiaohui; Zheng, Yu; Guo, Jinyun; Hao, Qijun; Xue, Yang (Frontiers in Earth Science, 2022)
In order to study the laws of crack evolution in rock and explain its fracture instability mechanism, a series of laboratory tests were carried out with Jinping Marbles. The test results show that the failure degree of marbles under unloading conditions is more severe than that under loading conditions. Based on volume crack strain, five progressive failure stages of crack evolution under different conditions are divided, and the corresponding characteristic stresses are determined. The pre-peak volume crack propagation strain without considering the initial damage is used to evaluate the pre-peak crack growth propagation degree of rock, and it is found that the lower the confining pressure, the higher the strain rate and unloading rate, the less the cracks generated before the peak, and the more the rock is prone to brittle failure after the peak. The starting point of the sharp increase of volume crack strain rate is proposed as the failure precursor point, and stress levels of failure precursor of marbles are in 70%–100%, which decrease as confining pressure, strain rate, and unloading rate rise. Under unloading conditions, failure precursor points appear later and are close to the unloading point, and unloading rocks are more prone to sudden brittle failure.